Distribution function of a distance between two random points in an oval - Gečiauskas, E. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Гячаускас. Функция распределения расстояния между внутри овала E. Gečiauskas, Atstumo tarp dviejų ovalo vidaus taškų pasiskirstymo funkcija